Pendampingan Kader Calon Pendakwah di kampus Universitas Prof. Dr. Hazairin, SH Bengkulu - Asfaruddin Asfaruddin; Nurlianti Nurlianti (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2020)
Assistance of Prospective Preacher Cadres at Universitas Prof. Dr. Hazairin SH Bengkulu Universitas Prof. Dr. Hazairin, SH Bengkulu (Unihaz) has a vision to become a lively, religious and excellent university in the implementation of the tridharma of higher education. Jum'at religi (Juri) is a student development program to create a religious atmosphere in campus life. This activity is integrated with Islamic religion courses by adding 1 credit for practicum. Efforts to reduce dependence with third parties in the implementation of the Juri, the ability of students, who are members of the Islamic Spirituality Unihaz Student Activity Unit, needs to be improved to become Juri guides from an early age. The aim of this program was to produce campus da'wah cadres who are ready to become the driving force for preaching on the Unihaz campus. Community service activities were carried out by means of training and guidance to read Al-Qur'an (tahsin) and worship training. Guidance was carried out periodically with the frequency of one meeting a week. The results that have been achieved from this program were that there was an increase in Islamic understanding and the ability to read the Al-Qur'an and the implementation of worship for participants, there is an increase in the activity of participants in participating in spiritual organization programs, there is an increase in the activity of participants to pray at mosques, and an increase in the number of participants. internal mentor in the implementation of the Juri program.